Status of Gastrointestinal Nematode Infections and Associated Epidemiological Factors in Sheep From Córdoba, Colombia - Brunal Tachack, Elisa; Oviedo Socarrás, Teresa; Oviedo Pastrana, Misael; Pérez Cogollo, Luis Carlos; Herrera Benavides, Yonairo; Rugeles Pinto, Clara; Vergara Garay, Oscar (Universidad de Córdoba - UCO, 2024)
Gastrointestinal nematodes cause serious economic losses in sheep production systems. To determine the prevalence and risk factors associated with these parasites, a study was conducted in 595 sheep in Córdoba, Colombia. Prevalence and parasite burden were determined using the McMaster technique. Larvae were cultured from feces to identify the nematode genera. For the analysis of associated factors and parasite burden, means, medians and confidence intervals were compared. A geo-referenced data analysis was performed and an epidemiological map was constructed. An overall prevalence of 88.2% was found, with the highest prevalence and parasite burden for Strongylida (83.2%) and Strongyloides (41%) nematodes. The mean parasite burden was 1255 eggs per gram. The gastrointestinal nematode genera identified were Trichostrongylus, Strongyloides, Haemonchus, Oesophagostomum, Bunostomum and Cooperia. In general, a significant association was found between parasite burden and dewormed animals, anthelmintic used, date of last deworming and breeds. The FAMACHA® method and body condition showed a significant association with Strongylida parasite burden. Clusters with higher intensity of gastrointestinal nematode burden and high prevalence were observed in the regions of Bajo Sinú, Sinú Medio and San Jorge.